Análisis de riesgos asociados a las empresas que utilizan la herramienta google drive (2021)
This bibliographic review article seeks to identify the different contributions from the point of view of strategy, the concern of organizations for security and the analysis of the risks they must have when using the Google Drive tool, since technology in the cloud has become a viable low cost and infrastructure solution. The contributions and support provided by the dynamic capabilities of the company, oriented to the market, with the use of different skills, methodologies applied with the discipline required in identifying market opportunities that arise for the company; for which a functional description of the tool is made with its advantages and disadvantages, risk analysis and present results of this analysis, in addition to the risks faced by organizations when using the GOOGLE DRIVE tool. Which is a resource of an innovation nature to organizational processes; likewise, during the development of this documentary research, the different contributions of organizational capacities were identified, with the contributions of the GOOGLE DRIVE tool, to the processes of strategic management of the company, without forgetting its main function, which is to stimulate business innovation in the markets